2004
DOI: 10.1021/jm030524k
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist Analogue of 6-[3‘-(1-Adamantyl)-4‘-hydroxyphenyl]-2-naphthalenecarboxylic Acid (AHPN) Family of Apoptosis Inducers That Effectively Blocks AHPN-Induced Apoptosis but Not Cell-Cycle Arrest

Abstract: The retinoid 6-[3'-(1-adamantyl)-4'-hydroxyphenyl]-2-naphthalenecarboxylic acid (AHPN) and its active analogues induce cell-cycle arrest and programmed cell death (apoptosis) in cancer cells independently of retinoic acid receptor (RAR) interaction. Its analogue, (E)-4-[3'-(1-adamantyl)-4'-hydroxyphenyl]-3-(3'-acetamidopropyloxy)cinnamic acid (3-A-AHPC) selectively antagonized cell apoptotic events (TR3/nur77/NGFI-B expression and nuclear-to-mitochondrial translocation) but not the proliferative events (cell-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(112 citation statements)
references
References 100 publications
3
106
0
Order By: Relevance
“…4D), also inhibited 3-Cl-AHPC-enhanced SHP association with the Sin3A complex (Fig. 5B) and blocked 3-Cl-AHPC-mediated apoptosis as we have previously shown (22). We speculated that if 3-Cl-AHPC binding to SHP plays an important role in 3-Cl-AHPC-mediated apoptosis, loss of SHP (Fig.…”
Section: Ahpn Binds To a Sin3a Complex(es)supporting
confidence: 67%
See 1 more Smart Citation
“…4D), also inhibited 3-Cl-AHPC-enhanced SHP association with the Sin3A complex (Fig. 5B) and blocked 3-Cl-AHPC-mediated apoptosis as we have previously shown (22). We speculated that if 3-Cl-AHPC binding to SHP plays an important role in 3-Cl-AHPC-mediated apoptosis, loss of SHP (Fig.…”
Section: Ahpn Binds To a Sin3a Complex(es)supporting
confidence: 67%
“…3-Cl-AHPC, (E)-4-[3 ¶-(1-adamantyl)-4 ¶-hydroxyphenyl]-3-(3 ¶-acetamidopropyloxy)cinnamic acid (3-A-AHPC) and [5,5 ¶-3 H 2 ] AHPN, were synthesized as described previously (14,22,23). [11, H 2 ]tRA was purchased from Perkin-Elmer Life Sciences (Boston, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggested that ARR-mediated growth inhibition and apoptosis seem to involve separate pathways (32,33). We found that exposure of cells to ARRs resulted in the enhanced association of SHP with the Sin3A complex and modification of the Sin3A complex with the enhanced binding of N-CoR, HDAC-4, and HSP90 and increased Sin3A-associated HDAC activity (27).…”
Section: Arr-mediated Apoptosis But Not Growth Inhibition Is Inhibitementioning
confidence: 59%
“…The prototype compound, 3Cl-AHPC, lacks activity against retinoid receptors, though having evolved from attempts to synthesize highly selective retinoid ligands. 44 3Cl-AHPC has demonstrated activity against cultured leukemia cells and in preclinical animal models of AML, 45,46 retaining activity even against retinoid refractory leukemia cell lines. 3Cl-AHPC appears to induce phosphorylation of TR3, possibly via a Jun N-terminal kinase (JNK) pathway, correlating with its exodus from the nucleus.…”
Section: Drug Discovery Strategies Directed At Core Components Of Thementioning
confidence: 99%